Velhos musicistas em ação: os efeitos da música em suas vidas - Lodovici Neto, Pedro (2009)
This study is based on a research in the qualitative approach of the musical practice in the interface of Anthropology and Gerontology. The purpose was to approach the nature of the musical pratice to detect what make this activity possible and the effects in the daily routine of elderly people, which use it as a professional or freelance practice or hobby. The aim of this study was to discuss how aged people experience and comprehend the music in general through the aspects that characterize this investigation: (i) the protagonism of the elderly musician, (ii) the oldness as a possible space in time for the musical practice, the music as an ideal habitant of body and soul; (iii) the music itself as a process that transcend taxonomies as erudite/popular, old/contemporary, instrumental/singing and must/can be presented in all course of the human life. 10 persons were interviewed (age between 67 and 88). Those persons were allocated in this study as belonging to 4 groups of active people and resident in the city of São Paulo: 2 musicians and music teachers (one of them retired), 4 members (retired or not) of a music group that frequently meet to play at a musical instruments shop in São Paulo downtown, 3 members (not retired) of a traditional jazz band and 1 retired maestro/musician out of the musical activity at this moment. The results point to three aspects about the music practice that make it possible and which effects can be clearly felt: the first one indicate the family side values which are central, the second one relies on the notion of productive activitythe music as a work rhythm increase and as a enthusiastic feature mainly in oldness-, and the last one, more pragmatic, presents the music as a valuable occupation and way of life. The variable gender showed a significant aspect in the different ways to say in the interview